(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The development of the industry is in line with technological advancements applied in the company. However, utilization of human labor in the industrial world in Indonesia is still needed, especially for manual material handling activities. This can cause a decrease in work productivity due to cumulative work injuries felt by the operator for a long period of time. This study aims to determine the critical work stations in causing muscle fatigue in the company XYZ by using the Nordic Body Map method. Based on the results of the study, the critical workstation is the Blowing Workstation, which obtains an average score of 7. This indicates that the workstation is critical to be repaired.